Pengembangan Permainan Halmakimia sebagai Media Pembelajaran Pada Materi Konfigurasi Elektron Kelas X MA atau SMA - Kurniati Kurniati (Universitas Negeri Padang, 2020)
This research aims to create and develop a game called halmakimia which can be used as a learning medium in the electron configuration material for class X MA or SMA. This study uses the type of Research and Development (R and D) with the 4D model. This model has 4 stages of research namely define, design, development, and disseminate. This study conducted a validity test and practicality test from the development stage. Halmakimia learning media is validated by 3 validators from the MAN 2 Bukittinggi chemistry teacher. The practicality questionnaire was filled by 33 student class X MAN 2 Bukittinggi and 2 chemistry teachers MAN 2 Bukittinggi. The results showed the validity test was 0.85 categorized very high. The kappa moment of 33 students MAN 2 Bukittinggi was 0.7 in the high practicality category, and MAN 2 Bukittinggi teachers were 0.83 in the very high category.